Per Capita Income, Market Access Costs, and Trade Volumes - Alexander Tarasov (Verein für Socialpolitik, 2010)
There is strong empirical evidence that countries with lower per capita income tend to have smaller trade volumes even after controlling for aggregate income. Furthermore, poorer countries do not just trade less, but have a lower number of trading partners. In this paper, I construct and estimate a general equilibrium model of trade that captures both these features of the trade data. There are two novelties in the paper. First, I introduce an association between market access costs and countries' development levels, which can account for the effect of per capita income on trade volumes and explain many zeros in bilateral trade flows. Secondly, I develop an estimation procedure, which allows me to estimate both variable and fixed costs of trade. I find that given the estimated parameters, the model performs well in matching the data. In particular, the predicted trade elasticity with respect to income per capita is close to that in the data.
Keywords: F12; F10; F14; 330; export zeros; fixed costs of trade; country extensive margin